The role of ultra-processed food consumption and depression on type 2 diabetes incidence: a prospective community study in Quebec, Canada - Akankasha Sen; Anne-Sophie Brazeau; Sonya Deschênes; Hugo Ramiro Melgar-Quiñonez; Norbert Schmitz (Public Health Nutrition, 2023)
Abstract